Contribution to the knowledge of the pharmaceutical ethnobotany of La Segarra region (Catalonia, Iberian Peninsula). (Journal of ethnopharmacology, 1997)
An ethnobotanical survey was carried out in the region known as La Segarra, situated at the north east of the Iberian Peninsula, in the inner plains of Catalonia, with an area of 720 km2 and a population of 17000. Working with 29 people, data on uses of 142 species belonging to 54 botanical families were obtained and presented, of which 13 uses corresponding to nine plant species were previously unreported.